Adaptive Learning Environments: A Requirements Analysis in Business Settings - Höver, Kai Michael; Steiner, Christina (International Journal of Advanced Corporate Learning (iJAC), 2009)
The design and development of an adaptive learning system (ALS) should be guided by a thorough analysis of usersâ?? expectations and needs. A requirements analysis has been carried out by means of scenario-based semi-structured interviews in order to investigate the personalization and adaptation preferences of different stakeholder groups in business settings. Results show that an ALS has a decided advantage over a non-adaptive learning system by offering individual treatment of learners. The adaptation of content and learning activities to learner knowledge and learning goal, particularly determined by the job role, is perceived to be most relevant.